Determinan Deteksi Financial Statement Fraud - Patmawati Patmawati; Meita Rahmawati; Muhammad Hidayat; Christian Damar Sagara Sitepu (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to empirically test the determinants of financial statement fraud detection with the Beneish M-Score, F-Score and Altman Z-Score models. The difference between this study and the previous study is that this study adds the F-Score model variable which is a financial statement fraud detection model developed using the scaled logistic probability technique. The population of this study is all banks listed on the Indonesia Stock Exchange. The samples in this study were perbankan that met the purposive sampling criteria. Based on the results of statistical tests obtained from the results of the study, the Beneish M-Score model has a significant effect on the financial statementt fraud variables, namely the Gross Margin Index (GMI) and the Asset Quality Index (AQI) variable while the Days Sales in Receivables Index (DSRI) variable, Leverage Index (LVGI), Total Accruals to Total Assets (TATA), and the Sales General and Administrative Expenses Index (SGAI) have no effect on the financial statement fraud variable. The F-Score variable states that only the Change in cash sales (Ch CS) variable has a significant effect on financial statement fraud while the change in receivable variable (Ch Rev), change in inventories (Ch Inv) and the change in earnings variable (Ch Ear) have a significant effect on the financial statement fraud variable. Meanwhile, the Altman Z-Score variable states that the Z-Score1 variable and the Z-Score3 variable have a significant effect on the financial statement fraud variable while the Z-Score2 variable and the Z-Score5 variable have no significant effect.